Role of Women in Good Governance - Showkat Ahmad Dar; Aadil Ahmad Shairgojri (Journal of Social Science, 2022)
The purpose of this study is to describe and analyse the significance of gender mainstreaming in good governance for the overall growth of the nation, with a particular emphasis on how gender engagement in decision making through consensus building and representation directly leads to women's empowerment. Qualitative study employed descriptive and analytic methods to achieve a conclusion by extensively utilising a thematic analytical tool. The concept of "good" governance requires making normative decisions about what constitutes the legal appropriation and efficient exercise of authority. Some organizations that offer outside assistance and social activists view good governance as implying democratic governance, which implies a focus on participation, human rights, and social justice. Good governance is more about the state's effectiveness than the justice of the economic system or the legitimacy of the political system. Decision-makers ability to act to improve the suffering of disadvantaged women or address the problem of gender inequality depends on how policies are implemented in practice. The process has only just begun with the signing of international agreements and the enactment of laws addressing issues like women's rights, equal access to education, marital rape, and credit and property ownership. The concept of "governance" clarifies the link between political commitment and a programme's successful and efficient implementation. Reform efforts for governance systems have received much attention recently. They are still receiving attention now on a national and international level.